Análise do transporte urbano em área central do município de Taboão da Serra - SP - Lopes, Isabela Magyar [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This thesis presents a study about the urban mobility of the city Taboão da Serra - SP. From the observation of the difficulties faced by the population while circulating in the central region of the city, especially in the rush hours, noticed that local analysis for a proposal of improvement in transportation planning were necessary. In order to do so, the main circulation problems and their contextualizations, were notified. A research Origin-Destination at the bus stops was also made to characterize the public transport. The analysis were made in two different fronts: non-motorized transport and motorized transport, following the same categorization of the traffic by the Brazilian Traffic Code. One of the main purposes of this work was to present general guidelines for the improvement of urban mobility in Taboão da Serra, as well as to identify the most frequent difficulties in the underdeveloped countries about the transportation. With this monograph, it is expected to create a reflection about the urban circulation in big cities, in order to promote a fairer transportation policy, guaranteeing an efficient circulation and a better quality of life for the population

Este trabalho apresenta um estudo sobre a mobilidade urbana do município de Taboão da Serra - SP. A partir da observação das dificuldades enfrentadas pela população ao circular na região central da cidade, principalmente no período de entrada e saída do trabalho, verificou-se a necessidade da análise local para uma proposta de melhoria no planejamento de transportes. Para tanto, notificou-se os principais problemas de circulação e suas contextualizações, juntamente com a realização da pesquisa Origem-Destino nos pontos de ônibus. A análise foi feita a partir de duas divisões: transporte não-motorizado e transporte motorizado, seguindo a mesma categorização do trânsito pelo Código de Trânsito Brasileiro. Um dos principais propósitos deste trabalho foi apresentar diretrizes gerais para a melhoria da mobilidade urbana em Taboão da Serra, bem como identificar as dificuldades mais frequentes nos países subdesenvolvidos com relação ao transporte. Com esta monografia, espera-se que haja uma reflexão sobre a circulação urbana em grandes cidades, de modo a fomentar uma política de transporte mais justa, garantindo uma circulação eficiente e maior qualidade de vida para a população
Analysis of urban transport in the central area of the municipality of Taboão da Serra - SP
Keywords: Transporte urbano; Planejamento urbano; Política de transporte urbano; Urban transportation